## Integrating Quadratic Denominators

In this page integrating quadratic denominators you are going to learn how to integrate quadratic equation which is in the denominator.

These kind of problems can be done in two ways. One is using direct formula and other one is using completing the square method.You can find both ways in this page integrating-quadratic- denominators.

Formula:

dx/(ax²+ bx + c)=(1/4a)[(2ax + b)²+(4ac - b²)]+c

Example 1:

Integrate 1/(x² + 5x + 7) with respect to x

Method 1:

∫ [ 1/(x² + 5x + 7) ] dx = ∫ dx/(x² + 5x + 7)

Now we have to compare the given quadratic equation (x² + 5x + 7) with (ax² + bx + c) then the values of a = 1, b = 5 and c = 7. Now we can use this formula to integrate the given function

Formula:

dx/(ax²+ bx + c)=4a/[(2ax + b)²+(4ac - b²)] dx

= 4(1)/ [ ((2(1)(x) + 5)² + (4(1) (7) - 5²) ] dx

= 4/[ (2x + 5)² + (28 - 5²) ] dx

= 4/[ (2x + 5)² + (28 - 25) ] dx

= 4 ∫1/ [ (2x + 5)² + 3 ] dx

= 4 ∫1/ [ (2x + 5)² + (√3)² ] dx

Now this exactly matches with one of the formula in standard integrals.

∫ dx/( a² + ) = (1/a) tan⁻ ¹ (x/a) + c

= 4 [1/(2x + 5) tan ⁻ ¹ [ √3/(2x + 5) ] + C

= [4/(2x + 5)] tan ⁻ ¹ [ √3/(2x + 5) ] + C

Method 2:

∫ [ 1/(x² + 5x + 7) ] dx = ∫ dx/(x² + 5x + 7)

With out using the direct formula we can just use the completing the square method for the quadratic equation.

For that let us take the quadratic equation which is in the denominator.

x² + 5x + 7 = x² + (2/2) 5x + 7

= x² + 2 x x x (5/2) + (5/2)² - (5/2)² +  7

= [ x + (5/2) ]² - (5/2)² +  7

= [ x + (5/2) ]² - (25/4) +  7

= { [ x + (5/2) ]² + (-25 + 28)/4 }

= { [ x + (5/2) ]² + 3/4 }

=  [ (2x + 5)/2) ]² + (√3/2)²

=   (2x + 5)²/4  + (√3)²/4

=   (1/4) [(2x + 5)²  + (√3)²]

Now we are going to apply (1/4) [(2x + 5)²  + (√3)²] for the quadratic equation (x² + 5x + 7)

So we will get ∫ [ 1/(x² + 5x + 7) ] dx = ∫ dx/(1/4) [(2x + 5)²  + (√3)²]

=  4 ∫ dx/[(2x + 5)²  + (√3)²]

∫ dx/( a² + ) = (1/a) tan⁻ ¹ (x/a) + c

Here a = (2x + 5)  x = √3

= 4 {1/[(2x + 5)] tan ⁻ ¹ [ √3/(2x + 5) ] }+ C

= [4/(2x + 5)] tan ⁻ ¹ [ √3/(2x + 5) ] + C

In both ways we will get the same answer.integrating quadratic denominators  integrating quadratic denominators

Related pages

Integrating Quadratic Denominators to Integration

Featured Categories

Math Word Problems

SAT Math Worksheet

P-SAT Preparation

Math Calculators

Quantitative Aptitude

Transformations

Algebraic Identities

Trig. Identities

SOHCAHTOA

Multiplication Tricks

PEMDAS Rule

Types of Angles

Aptitude Test